PENANGANAN SAMPAH RUMAH TANGGA MELALUI BUDIDAYA LARVA BLACK SOLDIER FLY (BSF) DI TPS 3R TIRTO ASRI PADUKUHAN MRISI, KELURAHAN TIRTONIRMOLO, KABUPATEN BANTUL - Nisa Fajria; Ayyub Kamal Hidayatullah; Alfine Alfarizhi; Muhamad Faisal Madani; Rinto Hermawan; Syaifana Adilla Ali; Inas Nur Faizah (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2022)
Dependence on imports of animal feed makes the price of animal feed expensive. On the other hand, feed costs are known to account for 70%-80% of the total production costs. This condition causes the production efficiency to be low. Utilization of alternative protein sources whose availability is abundant and does not compete with human food needs, is one of the promising solutions to optimize production efficiency. Various types of insects have the potential to be used to produce useful biomass, but the ones that have begin to be studied are the larvae of the Black Soldier Fly (BSF) or Hermetia illucens, the maggot/larvae of the house fly (Musca domestica) and the hongkong caterpillar. KKN (Community Service Program) members analyzed “Mrisi” for the cultivation of BSF larvae from looking for seeds, making a place for BSF larvae, mini experiments and distributing the harvest to the community. The BSF larvae cultivation program in Mrisi is proceeding as planned. TPS Tirto Asri has great potential in the process of cultivating BSF larvae. Good initial planning will result in good production too.